A comparison of chironomid biostratigraphy from Lake Vuolep Njakajaure with vegetation, lake-level, and climate changes in Abisko National Park, Sweden - Heinrichs, Markus; Barnekow, Lena; Rosenberg, Sandra (Journal of Paleolimnology, 2006)
Chironomid remains from the sediment of Lake Vuolep Njakajaure reflect limnological conditions resulting from changing climate and vegetation throughout the Holocene, but do not strictly follow accepted climate trends or the vegetation history based on regional pollen and macrofossil analyses. Chironomid community changes appear to be influenced by organic nutrient input from the surrounding catchment vegetation and lake hydrology, both of which are indirectly responding to some combination of climate change, hypolimnetic oxygen concentration, and changes in basin morphology. The chironomid-based quantitative mean July air-temperature reconstruction differs from other regional quantitative records; this discrepancy is likely related to limnological conditions particular to Lake Vuolep Njakajaure. Comparison of a northern Swedish temperature transfer function and one from western Canada reveals differences in the mean July air-temperature optima of several common taxa, suggesting that the existing conservative estimates of Holocene climate change in northern Sweden may be underestimated due to the limited temperature gradient captured by the Swedish training set.